A longitudinal, observational study of women who persisted in smoking in successive pregnancies. (4th January 2019) - Reynolds, C M E; Egan, B; O'Malley, E G; Kennedy, R A K; Sheehan, S R; Turner, M J
Abstract: Background: This longitudinal study examined the profile and pregnancy-related behaviours of women who reported smoking in two successive pregnancies when they presented for prenatal care in a large maternity hospital. Methods: Using the hospital electronic medical records, women who delivered two successive singleton pregnancies during the years 2011–15 were analyzed. Standardized data were computerized by a midwife at the first prenatal visit, following delivery and before discharge. Results: Over the 5 years, 6647 women delivered twice. Overall 5754 (86.6%) were persistent non-smokers in both pregnancies, 609 (9.2%) were persistent smokers in both pregnancies and between pregnancies 202 (3.0%) quit and 82 (1.2%) started smoking. Compared with persistent non-smokers, persistent smokers had higher rates of reported illicit drug use, alcohol consumption and psychological problems and lower rates of planned pregnancy, folic acid supplementation and breastfeeding in both pregnancies (all P < 0.001). In persistent smokers, folic acid supplementation practices deteriorated and illicit drug use increased in the subsequent pregnancy. Conclusions: We found that approximately one in 10 women smoked in two consecutive pregnancies. Furthermore, compared with non-smokers, persistent smokers were more likely to report other health behaviours associated with adverse pregnancy outcomes and may require additional multidisciplinary support.